2018
DOI: 10.1590/1983-1447.2017.03.2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Aprendizagens acadêmicas sobre saúde pública em uma universidade canadense: contribuições para a formação brasileira

Abstract: Public health learning in a Canadian university highlighted a great focus on determinants, allowing the students to think about Brazilian health care models. With this experience, discussions can be held in educational spaces, reflecting the social implication of Science without Borders Program in professional education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
(7 reference statements)
0
3
0
7
Order By: Relevance
“…The greatest lesson learned was that internationalization strategies must prioritize simplicity and agility in administrative procedures to use time productively and promote freedom to overcome budget and financing constraints. At the same time, it is expected that the availability of incentive programs for student 18 and professional mobility will be restored. In terms of social impact, we identify that nursing professionals'…”
Section: Discussionmentioning
confidence: 99%
“…The greatest lesson learned was that internationalization strategies must prioritize simplicity and agility in administrative procedures to use time productively and promote freedom to overcome budget and financing constraints. At the same time, it is expected that the availability of incentive programs for student 18 and professional mobility will be restored. In terms of social impact, we identify that nursing professionals'…”
Section: Discussionmentioning
confidence: 99%
“…integralidade, universalidade e equidade (6) . A proposta do modelo brasileiro é um sistema descentralizado, funcionando em níveis de complexidade, no qual a porta de entrada é a atenção primária, podendo existir a complementação da iniciativa privada (6) .…”
Section: Convergências E Divergências Da Prática Do Enfermeiro Na Atenção Primáriaunclassified
“…O acesso à saúde pública no Canadá possui princípios semelhantes ao do SUS, sendo também universal, ou seja, todos os cidadãos canadenses possuem acesso à saúde, e cobertura dos serviços de saúde necessários médicos e hospitalares, e assim como no Brasil, financiado pelos impostos, dos quais, em contraposição, 70% são voltados para à saúde (6) .…”
Section: Convergências E Divergências Da Prática Do Enfermeiro Na Atenção Primáriaunclassified
See 1 more Smart Citation
“…Reporting an undergraduate exchange experience, Patuzzi et al 12 demonstrated that this experience engages the construction of new management and planning prospects in the SUS, bearing in mind that the doctors and nurses take on this responsibility in their professional role. Furthermore, such internationalization allows the academic to observe possible innovations, for instance, the identification of new ways of acting and thinking as regards health and citizenship.Although the learning process and understanding of how other educational institutions and health services are organized do represent a challenge, as one must transcend preconceived ideas and consider the diverse contexts that culturally and socioeconomically engage each location.…”
mentioning
confidence: 99%